Increased Dendritic Orientation Dispersion in the Left Occipital Gyrus is Associated with Atypical Visual Processing in Adults with Autism Spectrum Disorder. (9th June 2020) - Matsuoka, Kiwamu; Makinodan, Manabu; Kitamura, Soichiro; Takahashi, Masato; Yoshikawa, Hiroaki; Yasuno, Fumihiko; Ishida, Rio; Kishimoto, Naoko; Yasuda, Yuka; Hashimoto, Ryota; Taoka, Toshiaki; Miyasaka, Toshiteru; et al.
Abstract: In autism spectrum disorder (ASD), the complexity-specific hypothesis explains that atypical visual processing is attributable to selective functional changes in visual pathways. We investigated dendritic microstructures and their associations with functional connectivity (FC). Participants included 28 individuals with ASD and 29 typically developed persons. We explored changes in neurite orientation dispersion and density imaging (NODDI) and brain areas whose FC was significantly correlated with NODDI parameters in the explored regions of interests. Individuals with ASD showed significantly higher orientation dispersion index (ODI) values in the left occipital gyrus (OG) corresponding to the secondary visual cortex (V2). FC values between the left OG and the left middle temporal gyrus (MTG) were significantly negatively correlated with mean ODI values. The mean ODI values in the left OG were significantly positively associated with low registration of the visual quadrants of the Adolescent/Adult Sensory Profile (AASP), resulting in a significant positive correlation with passive behavioral responses of the AASP visual quadrants; additionally, the FC values between the left OG and the left MTG were significantly negatively associated with reciprocal social interaction. Our results suggest that abnormal V2 dendritic arborization is associated with atypical visual processing by altered intermediation in the ventral visual pathway.